Formulation and Evaluation of Body Lotion Preparation from Ethanol Extract of Avocado Leaves (Persea americana Mill.) as Antioxidant with DPPH Method - Putri Nuraimun Simanjuntak; Herlina Herlina; Barita Aritonang; Hasni Yaturramadhan Harahap (Jurnal FARMASIMED (JFM), 2025)
Skin damage is a common problem that can affect appearance and health. Excessive exposure to free radicals from UV rays is one of the main causes of skin damage, the use of body lotions containing natural antioxidant compounds is very important to protect the skin from these effects. Avocado leaves (Persea americana Mill.) have been known to contain antioxidant chemicals that are good for skin protection, one of which is flavonoids. The purpose of this study was to determine whether avocado leaf body lotion preparations can function as antioxidants and to develop body lotion preparations that meet the evaluation test requirements. The research stages included the preparation of simple drugs, the preparation of avocado leaf extract, the test of antioxidant functional groups with UV-Vis and FTIR spectroscopy, the preparation of avocado leaf ethanol extract body lotion, the evaluation of body lotion preparations, and the testing of antioxidant activity of body lotions using the DPPH method. The results of the phytochemical analysis revealed the presence of tannins, alkaloids, saponins, and flavonoids. Avocado leaf extract body lotion was formulated in four concentration variations (0%, 2%, 4%, and 6%). All formulas meet SNI, with a pH of 7 and a spreadability of between 5-7 cm. Antioxidant activity tests showed a decreasing IC50 value with increasing extract concentration: 12.4643 µg/mL (2%), 4.6300 µg/mL (4%), and 1.1065 µg/mL (6%), which are categorized as very strong. The formulation with a concentration of 6% showed stronger activity. The conclusion of this study indicates that lotion made from avocado leaf extract has the potential as a skin care product with very strong antioxidant capabilities.